Analisis Keuntungan Usaha Rumah Makan “Tinutuan Marlan” Di Keluarahan Bahu Kecamatan Malalayang Kota Manado - Wenda, Depius; Jocom, Sherly Gladys; Kaunang, Rine (Sam Ratulangi University, 2024)
This study aims to analyze the profitability of “Tinutuan Marlan” Restaurant in Bahu, Malalayang District, Manado City. The research was conducted over a period of 3 (three) months from September to November 2023 at “Tinutuan Marlan” Restaurant in Bahu, Malalayang District, Manado City. Primary data for this study were obtained through direct interviews with the owner of “Tinutuan Marlan” Restaurant, using a questionnaire as a data collection tool. Secondary data included business records from “Tinutuan Marlan” Restaurant and internet sources such as journals. The collected data were analyzed descriptively and presented in tabular form. Data analysis in this study included production cost analysis, revenue analysis, and profit analysis. The results of the study indicate that “Tinutuan Marlan” Restaurant in Bahu, Malalayang District, Manado City is profitable. The total weekly revenue received is IDR6,126,000, total weekly expenses are IDR3,428,250, resulting in a weekly profit of IDR2,697,750. For daily calculations over 6 days a week, the restaurant receives IDR1,021,000 per day in revenue, incurs IDR571,375 in daily expenses, and achieves a daily profit of IDR449,625.